Theory of Legal Transformation in Sharia Economic Law - Hari Rahmat Mulyadin; Hasan Bisri; Ayi Yunus Rusyana (Yayasan Mentari Madani, 2023)
This journal investigates the theory of legal transformation in the perspective of Islamic economic law. Legal transformation in the context of Islamic economics is a significant phenomenon as it involves changes in regulations and economic practices that are in accordance with Islamic principles. This study aims to understand legal changes in the context of Islamic economics by integrating legal transformation theory and Islamic legal perspectives. The introduction explains that Islamic economics has taken center stage in various countries with a majority Muslim population as well as in non-Muslim countries. Legal transformation in the context of Islamic economics involves the development of laws, regulations, policies, and legal interpretations that enable Islamic financial and investment practices that are in accordance with sharia principles. However, a proper theoretical approach is needed to understand these legal changes comprehensively. This journal adopts a theoretical approach in analyzing legal transformation in the perspective of Islamic economic law. The factors driving legal change, such as social, political, and economic developments, are explored in the context of Islamic economics. In addition, the role of legal institutions in generating changes and implementation of sharia economic law is also discussed. The impact and implications of legal transformation in Islamic economic practices are analyzed in depth. This research discusses how legal changes affect Islamic economic policies, the development of Islamic financial institutions, and their impact on the economic life of Muslims. Challenges and obstacles in the transformation of sharia economic law were also identified, such as differences in legal interpretation, tensions between sharia principles and non-sharia regulations, and political and social constraints. This journal makes a significant contribution in the understanding of the theory of legal transformation in the perspective of Islamic economic law. The results of this research can be used by governments, regulators, financial institutions, and civil society to strengthen the regulatory framework, increase harmonization of sharia principles with economic policies, and encourage sharia economic growth in accordance with Islamic principles.